Trotskyists on Trial : Free Speech and Political Persecution Since the Age of FDR - Haverty-Stacke, Donna T. (Book collections on Project MUSE., 2015)
The Smith Act was a peacetime anti-sedition law that marked a dramatic shift in the legal definition of free speech protection in America by criminalizing the advocacy of disloyalty to the government by force. It also criminalized the acts of printing, publishing, or distributing anything advocating such sedition and made it illegal to organize or belong to any association that did the same. It was first brought to trial in July 1941, when a federal grand jury in Minneapolis indicted 29 Socialist Workers Party members, 15 of whom also belonged to the militant Teamsters Local 544. 18 of the defendants were convicted of conspiring to overthrow the government. Examining the social, political, and legal history of the first Smith Act case, this book focuses on the tension between the nation's cherished principle of free political expression and the demands of national security.